Sistem Informasi Rekam Medis Klinik Kasih Murni Berbasis web - Anjis Ilham Rahmatdani Ilham (LPPM Universitas Merdeka Madiun, 2024)
In the midst of the rapid advancement of information and communication technology, fast and accurate information is increasingly becoming the main need for decision makers. In other words, information is a basic requirement required by every management to make decisions. Even a hospital as an institution that stores a lot of data also requires correct and accurate data processing that can be presented in such a way in the form of a report. Presentation of reports in the form of information must be in accordance with the value of the use and function of each part. One of them is a web-based medical record information system. In this study, the design and analysis techniques in the manufacture used the Waterfall method. This system has been tested using black box testing to get the expected results and the system is feasible to use. Based on the results of the description and discussion of the final project report, a Medical Record Information System has been successfully built in the Kasih Murni clinic for monitoring health in Website-Based Children using the waterfall method and the code igniter framework with the PHP programming language. The system is expected to be able to assist in processing medical records in clinics and hospitals where as long as the recording of medical record data is still done manually.